2009
DOI: 10.1007/s00420-009-0415-8
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in nasal lavage from hairdressers exposed to persulphate

Abstract: ObjectivesMany hairdressers experience work-related symptoms from the airways caused by bleaching powder. This contains persulphates, which could be irritating to the mucous membrane and also may evoke an allergic reaction. However, specific IgE antibodies are difficult to detect.We found earlier that hairdressers with work-related bleaching powder-associated nasal symptoms reacted to persulphate, but that atopics also did and that the mechanism appeared to be similar in the two groups. In this study, we analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…No specific IgE antibodies were found and it was suggested that the reaction was driven by Th1 cell activation. Jönsson et al found an altered gene expression of cytokines when analyzing mRNA in nasal lavage from the same subjects . They detected an increase in IL-5 in the symptomatic as well as the atopic group, suggesting eosinophilic activation.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…No specific IgE antibodies were found and it was suggested that the reaction was driven by Th1 cell activation. Jönsson et al found an altered gene expression of cytokines when analyzing mRNA in nasal lavage from the same subjects . They detected an increase in IL-5 in the symptomatic as well as the atopic group, suggesting eosinophilic activation.…”
Section: Discussionmentioning
confidence: 98%
“…Jo ¨nsson et al found an altered gene expression of cytokines when analyzing mRNA in nasal lavage from the same subjects. 8 They detected an increase in IL-5 in the symptomatic as well as the atopic group, suggesting eosinophilic activation. In the latter group, an increase in IL-13 expression was also seen.…”
Section: Nasal Lavage Of Hairdressersmentioning
confidence: 94%
See 2 more Smart Citations
“…However, nasal response showed some differences. Hairdressers with rhinitis to bleach showed increases in apolipoprotein A1, IL-5, IFN-Y in post SIC nasal lavage, while, in atopics, an increase in IL-5 and IL-13 was found (Diab et al 2009 ; Jonsson et al 2009 ; Karedal et al 2010 ). One study showed positive SIC to PS in one out of eight control subjects with asthma not caused by PS, no positive SIC in ten healthy control subjects, in contrast to six (among these five hairdressers) out of eight subjects with asthma and occupational exposure to PS (Munoz et al 2004 ).…”
Section: Occupational Rhinitis and Asthma Caused By Persulphatesmentioning
confidence: 99%